2018
DOI: 10.3390/rs10071115
|View full text |Cite
|
Sign up to set email alerts
|

Satellite and Ground Remote Sensing Techniques to Trace the Hidden Growth of a Lava Flow Field: The 2014–2015 Effusive Eruption at Fogo Volcano (Cape Verde)

Abstract: Fogo volcano erupted in 2014-2015 producing an extensive lava flow field in the summit caldera that destroyed two villages, Portela and Bangaeira. The eruption started with powerful explosive activity, lava fountains, and a substantial ash column accompanying the opening of an eruptive fissure. Lava flows spreading from the base of the eruptive fissure produced three arterial lava flows. By a week after the start of the eruption, a master lava tube had already developed within the eruptive fissure and along th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 70 publications
1
22
0
Order By: Relevance
“…At the beginning of many basaltic fissure eruptions, the discharge rate increases rapidly to a maximum value, then gradually drops to lower values as the eruption proceeds and the feeder dike empties [Wadge, 1981]. This behaviour has been observed and documented at several basaltic effusive eruptions and on different volcanoes, such as Etna and Stromboli (Italy), Fogo (Cape Verde), Holhuraun (Iceland), Piton de la Fournaise (La Réunion), Kilauea (Hawaii), [Hon et al, 1994;Calvari et al, 2005Calvari et al, , 2018Harris et al, 2005aHarris et al, , 2011Harris et al, , 2012Lodato et al, 2007;Spampinato et al, 2008aSpampinato et al, , 2008bGanci et al, 2012aCappello et al, 2016;Coppola et al, 2017;Patrick et al, 2017;Pedersen et al, 2017]. The general trend of declining discharge rate is overlapped by a local variability giving rise to pulses of the order of hours along the lava flow channel [Lautze et al, 2004;Bailey et al, 2005;Harris et al, 2005b], that re-FIGURE 2.…”
Section: Tadr Er Iermentioning
confidence: 76%
See 4 more Smart Citations
“…At the beginning of many basaltic fissure eruptions, the discharge rate increases rapidly to a maximum value, then gradually drops to lower values as the eruption proceeds and the feeder dike empties [Wadge, 1981]. This behaviour has been observed and documented at several basaltic effusive eruptions and on different volcanoes, such as Etna and Stromboli (Italy), Fogo (Cape Verde), Holhuraun (Iceland), Piton de la Fournaise (La Réunion), Kilauea (Hawaii), [Hon et al, 1994;Calvari et al, 2005Calvari et al, , 2018Harris et al, 2005aHarris et al, , 2011Harris et al, , 2012Lodato et al, 2007;Spampinato et al, 2008aSpampinato et al, , 2008bGanci et al, 2012aCappello et al, 2016;Coppola et al, 2017;Patrick et al, 2017;Pedersen et al, 2017]. The general trend of declining discharge rate is overlapped by a local variability giving rise to pulses of the order of hours along the lava flow channel [Lautze et al, 2004;Bailey et al, 2005;Harris et al, 2005b], that re-FIGURE 2.…”
Section: Tadr Er Iermentioning
confidence: 76%
“…The lava flow field initially emplaced as thin pahoehoe lobes that gradually coalesced into larger sheet lobes [Guilbaud et al, 2005], an expansion similar to most pahoehoe lava flow fields observed today on Kilauea [Hon et al, 1994;Kauahikaua et al, 1998;Patrick et al, 2017]. At basaltic volcanoes like Etna and Stromboli (Italy), Kilauea (Hawaii), Piton de la Fournaise (La Réunion), Fogo (Cape Verde), or Holuhraun (Iceland), the general shape of a complex lava flow field is defined by a few arterial lava flows generally displaying aa texture, with its outline modified by secondary lava flows normally having a pahoehoe surface [Guest et al, 1987;Lopes, 1988, 1991;Calvari et al, 2005Calvari et al, , 2018Rhéty et al, 2017;Pedersen et al, 2017]. When lava tubes develop within complex lava flows, their hidden path is revealed by the distribution of skylights, ephemeral vents or breakouts, tumuli, shatter rings, or pressure ridges [Guest et al, 1980;Mattox et al, 1993;Calvari and Pinkerton, 1998;Kauahikaua et al, 1998Kauahikaua et al, , 2003Calvari et al, 1994Calvari et al, , 2018.…”
Section: Flow Front Velocity M S -1 Referencementioning
confidence: 99%
See 3 more Smart Citations